Nucleotide sequence of the thrA gene of Escherichia coli. - Katinka, M (1980)
The thrA gene of Escherichia coli codes for a single polypeptide chain having two enzymatic activities required for the biosynthesis of threonine, aspartokinase I and homoserine dehydrogenase I. This gene was cloned in a bacterial plasmid and its complete nucleotide sequence was established. It contains 2460 base pairs that encode for a polypeptide chain of 820 amino acids. The previously determined partial amino acid sequence of this protein is in good agreement with that predicted from the nucleotide sequence. The gene contains an internal sequence that resembles the structure of bacterial ribosome-binding sites, with an AUG preceded by four triplets, each of which can be converted to a nonsense codon by a single mutation. This suggests that the single polypeptide chain was formed by the fusion of two genes and that initiation of translation may occur inside the gene to give a protein fragment having only the homoserine dehydrogenase activity.